The prevention and punishment of abuse of fixed-term employment contracts in the public administrations. Comment on the judgement of the Court of Justice of the European Union of 19 March 2000 (joined cases C-103/18, C-429/18) - Gómez Abelleira, Francisco Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The endemic problem of abuse of fixed-term employment contracts in the Spanish public administrations leads to a new judgment of the Court of Justice of the European Union, which holds that the renewal of fixed-term contracts to meet permanent needs is against the letter and purpose of Directive 1999/70. The judgement examines the efficacy of other equivalent legal measures to prevent abuses, such as the transformation of the temporary relationship into a “temporary relationship with a contract of indefinite duration”; this measure is not appropriate for the purpose of attaining the objective pursued by clause 5 of the Framework Agreement. Worker’s consent cannot be construed as removing the abusiveness of the employer’s behavior.